SIMPSON TYPOLOGY OF NARRATORS APPLIED IN PANCHATANTRA’S THE CLEVER HARE - Agnes Widyaningrum . (Dinamika Bahasa dan Budaya, 2018)
Children’s stories consist of colorful and beautiful illustration to support the children’s understanding when they read the stories. As the readers they will be interested if the story books whom they read are easy for them to comprehend. The way the children read the book might be different especially when their parents involved in reading stories for them as bed time stories. Sometimes their parents used their own way in reading the stories as they are the characters in the stories. Instead of reading it they are telling it. Simpson (1993) develops a typology of narrators based on the modality of the discourse. Modality is particularly important because of its strongly interpersonal function (Black, Elizabeth, 2006:55). When the story makers tell the story they have the function as the participants in the story (first person narrative or type A) on the contrary the third person narrators belong to type B.Keywords: narrators, typology or narrators, first person narrators, third person narrators